Interação bi-direcional entre sono e crescimento tumoral em camundongos - Maragno-Correa, Jussara Maria Ragonezzi [UNIFESP] (2010)
The interactions between sleep and immune system have been investigated for years. Within this context, studies have been conducted in order to investigate the importance of sleep and the impact of sleep loss in health. Thus, it is well-known that sleep disorders are highly prevalent in cancer patients and that their sleep quality is impaired. Notwithstanding, a great amount of evidence have suggested that the sleep disorders-induced immunologic impairments could contribute to tumoral growth, affecting the prognostic and mortality of cancer patients. In this way, the aim of the present study was to investigate the interactions among sleep, immune system and Ehrlich ascitic tumor growth. Male or female BALB/c mice were subjected to sleep deprivation for 72h by multiple platforms technique immediately before or after the Ehrlich ascitic tumor inoculation. We verified that previous sleep deprivation potentiated the subsequent tumor growth both in male or female mice. Importantly, the Ehrlich ascitic tumor-induced immunological impairments were exacerbated by sleep deprivation. In addition, when sleep deprivation occurred immediately after tumor inoculation, this potentiating effect (enhanced tumor growth) was delayed in male mice. At last, but not least, in female mice, the same sleep deprivation protocol did not modify Ehrlich ascitic tumor growth but remarkably curtailed life span of these animals.